An Analysis of Metaphors on Noel Gallagher at High Flying Birds Album - Rajamin Keposan Lingga; Sanggam Siahaan; Bloner Sinurat (Indonesian Journal Education, 2025)
This study analyzes the use of metaphors in Noel Gallagher’s High Flying Birds album, aiming to classify the types of metaphors employed in the song lyrics and uncover their underlying meanings. The research examines ten songs using a descriptive qualitative approach, drawing on Lakoff and Johnson’s (1980) Conceptual Metaphor Theory as the primary analytical framework. The lyrical data were collected from publicly available sources and analyzed through data reduction, data display, and conclusion drawing based on Miles and Huberman’s (1994) model. The findings reveal three dominant metaphor types—ontological, structural, and orientational with structural metaphors appearing most frequently. These metaphors function as symbolic representations of emotional and existential themes such as struggle, identity, love, and resilience. Gallagher often translates abstract concepts into concrete imagery such as light, roads, storms, and clocks—enabling listeners to perceive complex human experiences in a tangible manner. The study concludes that metaphors in High Flying Birds serve not merely as stylistic devices but as cognitive tools that shape listeners’ understanding of life and emotional realities. This research contributes to semantic studies by demonstrating how conceptual metaphors in song lyrics construct meaning beyond literal interpretation and reinforce music’s role as a medium of cultural and emotional expression.